2021
DOI: 10.1044/2021_ajslp-20-00380
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Workplace Diversity Through the Culturally Responsive Teamwork Framework

Abstract: Purpose Diversification of the profession is an important element of combating racism, bias, and prejudice in the speech-language pathology workforce at national and systemic levels. However, national and systemic change needs to be combined with equipping individual speech-language pathologists to adapt to the challenges that they face to engaging in culturally responsive practice. This paper presents four interacting levels of practice within the Culturally Responsive Teamwork Framework (CRTF): (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Nine studies were an evaluation of either a Hanen‐developed professional development program (eg, Learning Language and Loving It 12 ) or an adapted version of a Hanen‐developed program (eg, 13 ); two studies reported an unnamed coaching‐based professional development program, and one study reported outcomes of the Structured Preschool Efforts in Language and Literacy (SPELL), a program adapted from Read It Again‐PreK! (RIA 14 ). Most programs (n = 10) included a workshop component and most (n = 10) included at least one consultation‐style mentoring session where an early childhood educator was provided with feedback on their use of different interaction strategies taught during the training.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were an evaluation of either a Hanen‐developed professional development program (eg, Learning Language and Loving It 12 ) or an adapted version of a Hanen‐developed program (eg, 13 ); two studies reported an unnamed coaching‐based professional development program, and one study reported outcomes of the Structured Preschool Efforts in Language and Literacy (SPELL), a program adapted from Read It Again‐PreK! (RIA 14 ). Most programs (n = 10) included a workshop component and most (n = 10) included at least one consultation‐style mentoring session where an early childhood educator was provided with feedback on their use of different interaction strategies taught during the training.…”
Section: Resultsmentioning
confidence: 99%
“…We are not the first to suggest the speech-language therapy profession needs a new way forward (see also Hopf et al, 2021;Khoza-Shangase & Mophosho, 2021). The COVID-19 http://www.sajcd.org.za Open Access pandemic has forced us to confront ongoing global inequities in health care, education and employment sectors.…”
Section: Discussionmentioning
confidence: 99%
“…In those communities and sectors without SLTs, cross-sectoral collaboration is essential to improve communication support and services (Hopf, Crowe, Verdon, Blake, & McLeod, 2021 ; Wylie et al, 2018 ). How we as a profession choose to engage with community stakeholders will influence how CD is understood and the type of advice and support available or needed in the community.…”
Section: Provocative Statements For Moving Forwardmentioning
confidence: 99%
“…Performance monitoring is indispensable for tracking progress, pinpointing areas for improvement, and motivating employees by showcasing tangible impacts [30]. The imperative of continuous education and training is highlighted for empowering workers to recognize and control hazards, with advancements in learning methodologies providing efficient training delivery [31,32].…”
Section: Fostering a Culture Of Continuous Improvementmentioning
confidence: 99%